PENGARUH GEDUNG HIJAU TERHADAP EFISIENSI ENERGI GEDUNG - Pieter Kevin Kristanto; Susanti Widiastuti; Suryono Herlambang (Jurusan Arsitektur dan Perencanaan, 2026)
As advancements in technology and increasing spatial demands reshape the built environment, building management practices have undergone substantial adjustments, particularly in relation to growing environmental concerns. Within the property sector, issues of energy utilization and cost efficiency have become significantly more prominent over the past fifteen years. Rising operational requirements have driven the adoption of assessment frameworks such as Green Building certification, which evaluates the extent to which a building adheres to comprehensive sustainability principles. Beyond improving the environmental quality experienced by occupants, this certification supports building owners and managers in reducing operational expenditures through enhanced energy performance and the implementation of more efficient systems. Nevertheless, the measurable impact of such certification varies across buildings, influenced by climatic conditions, occupancy behavior, and daily facility management practices. This study seeks to assess the contribution of Green Building certification to energy efficiency, with particular emphasis on the Indonesian context, characterized by a tropical climate and high levels of electricity and water consumption. The analysis further examines the role of building facilities, utilities, and operational procedures in shaping energy use, and incorporates benchmarking comparisons between certified and non-certified buildings. The findings are expected to offer more definitive insights into the actual effectiveness of green building practices and to inform the development of more sustainable and renewable energy management strategies for future building operations. Keywords: energy efficiency; green building; property management Abstrak Seiring berkembangnya teknologi dan kebutuhan akan ruang, pengelolaan gedung mengalami banyak penyesuaian, salah satunya ialah meningkatnya perhatian terhadap isu lingkungan. Dalam sektor properti, perhatian terhadap penggunaan energi dan efisiensi biaya semakin menonjol dalam lima belas tahun terakhir. Peningkatan kebutuhan operasional mendorong munculnya standar penilaian seperti sertifikasi Green Building, yang berfungsi menilai apakah sebuah bangunan telah menerapkan prinsip keberlanjutan secara menyeluruh. Sertifikasi ini tidak hanya memberikan kualitas lingkungan yang lebih nyaman bagi penyewa, tetapi juga membantu pemilik dan pengelola gedung menekan biaya operasional melalui penghematan energi serta pemanfaatan sistem yang lebih efisien. Meski demikian, dampak sertifikasi tidak selalu sama pada setiap gedung, karena hasilnya sangat dipengaruhi oleh kondisi iklim, pola penggunaan ruang, serta cara pengelolaan fasilitas sehari-hari. Penelitian ini bertujuan menilai sejauh mana sertifikasi Green Building berkontribusi pada efisiensi energi, khususnya dalam konteks Indonesia yang memiliki iklim tropis dan intensitas penggunaan energi listrik dan air yang sangat tinggi. Analisis juga mencakup pengaruh fasilitas, utilitas, dan prosedur operasional terhadap konsumsi energi, serta perbandingan kinerja energi antara gedung bersertifikat dan non-sertifikat melalui metode benchmarking. Temuan pada penelitian diharapkan dapat memberi penjelasan yang lebih baik dan lengkap mengenai efektivitas penerapan konsep bangunan hijau dan membantu menyusun strategi pengelolaan energi yang lebih berkelanjutan dan terbarukan di masa depan.